The Role of Public Administration in Preventing Corruption of State Officials - Firmansyah, Vicky Zaynul; Syam, Firdaus (Jurnal Magister Administrasi Publik, 2021)
The main problem with the Indonesian government is the behavior of deviant acts of corruption that harm the nation and state. This research is shown to prevent acts of corruption by implementing the principles of public administration in state officials. The research method used, namely the type of quantitative research is comparative experimental. There are various policies taken by the government to prevent corrupt behavior, namely the application of the principles of public administration in state officials, ethical development and bureaucratic governance through the development of good governance, enforcement and application of public administration law, public awareness, and participation, efforts to improve the system. more effective and efficient public services, and the establishment of an independent institution to prevent corruption. However, this study found irregularities in the efforts to strengthen the KPK institution by re-doing the national insight test on employees.